Quantitative Structure-Mobility Relationship Prediction of Electrophoretic Mobilities of Some Organic Acids, Amino Acids and Carbohydrates - FATEMI, M.H.; HADJMOHAMMADI, M.R.; BARARJANIAN, F. (Asian Journal of Chemistry, 2010)
Based on theoretical calculated molecular structural descriptors from the solute's structure alone, the electrophoretic mobility of 67 solutes including 23 organic acids, 18 amino acids and 26 carbohydrates in capillary electrophoresis were predicted. In order to find the best model, heuristic method was used to build several multivariable linear models using different numbers of molecular descriptors. This model gave the following statistical values; the square of correlation coefficient R2 was 0.968, standard error was 0.0778 and the statistical F-value of 380.82. Descriptors which appeared in the selected model can account the hydrodynamic and dielectric friction forces which affected on the electrophoretic mobility of solute. Also in order to evaluate the credibility of model the leave one cross-validation test and Y-scrambling method were employed. The statistically results obtained by these tests reveals the reliability of constructed model.